Stimulation of protective and cross-protective immunity against influenza B virus after adjuvant mucosal immunization of mice - Prokesová, L; Zanvit, P; Havlícková, M; Tácner, J; Jirkovská, M; Petrásková, P; Novotná, O; Cechová, D; Julák, J (Folia microbiologica, 2009)
Intratracheal immunization of mice with inactivated influenza B virus and delipidated Bacillus firmus as adjuvant increases protection of mice against infection with the homologous virus strain and induces cross-protection: mice immunized by influenza virus B/Yamanashi 166/98 were protected even against phylogenetically distant virus drift variant B/Lee/40 lethal for mice.
Keywords: analýza přežití; Orthomyxoviridae Infections; Administration, Inhalation; Mice, Inbred BALB C; aplikace inhalační; Influenza B virus; Vaccines, Inactivated; Bacillus; Survival Analysis; vakcíny proti chřipce; Mice; Influenza Vaccines; inaktivované vakcíny; virus chřipky B; Cross Protection; ženské pohlaví; Immunization; zvířata; myši inbrední BALB C; infekce viry z čeledi Orthomyxoviridae; myši; zkřížená ochrana; adjuvancia imunologická; Adjuvants, Immunologic; imunizace; Female; Animals